Pengaruh Literasi Numerasi Dan Efikasi Diri Terhadap Indeks Prestasi Kumulatif - Irajuana Haidar (Departement of Mathematics Education, 2023)
This research aims to explore the influence of numeracy literacy and self-efficacy on the Cumulative Achievement Index among students enrolled in the Mathematics Education Study Program at the University of Nineteen November Kolaka, class of 2020. Using a quantitative method, the research analyzed data through multiple regression with the aid of SPSS software. The findings revealed a notable combined impact of numeracy literacy and self-efficacy on the Cumulative Achievement Index.However, individually, the numerasi literacy variable has no impact on the Cumulative Performance Index. In contrast to the self-efficacy variable which shows that there is a significant influence on the Cumulative Performance Index. The results of this finding are interesting enough to be used as a valuable guideline to find out more deeply what factors or indicators can be developed to create graduates who have better academic performance.